Baggage Handling / A Key Performance Indicator for Airports - Marques Da Silva Fabio; Mendes Peixoto Kleyton (International Airport Review, 2021)
Why 'Security Thinking' has Never Been More Important, CANSO's DG on a New Future for Aviation, An Innovative and Contactless Airport Experience in Bahrain.